2012
DOI: 10.1083/jcb.201201139
|View full text |Cite
|
Sign up to set email alerts
|

The FATP1–DGAT2 complex facilitates lipid droplet expansion at the ER–lipid droplet interface

Abstract: A complex between the ER resident protein FATP1 and the lipid droplet–localized DGAT2 protein facilitates lipid droplet expansion in C. elegans and mammalian cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
215
0
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 247 publications
(223 citation statements)
references
References 61 publications
(107 reference statements)
6
215
0
2
Order By: Relevance
“…The reduction of PC levels in the asm-3(ok1744) mutant embryos was remarkable because a decrease of this lipid class increases the size of the lipid droplets in the intestine of adult worms (Krahmer et al 2011;Xu et al 2012;Ehmke et al 2014). This also could be the reason for lipid droplet enlargement in the asm-3 mutant embryos.…”
Section: Discussionmentioning
confidence: 97%
“…The reduction of PC levels in the asm-3(ok1744) mutant embryos was remarkable because a decrease of this lipid class increases the size of the lipid droplets in the intestine of adult worms (Krahmer et al 2011;Xu et al 2012;Ehmke et al 2014). This also could be the reason for lipid droplet enlargement in the asm-3 mutant embryos.…”
Section: Discussionmentioning
confidence: 97%
“…Furthermore, DGAT2 appears to be part of a large heterologous protein complex (Ͼ650 kDa) as co-immunoprecipitation experiments have shown that DGAT2 can interact with two proteins, FATP1 and SCD1 (9,23,24). Both of these enzymes catalyze the synthesis of substrates utilized by DGAT2 for TG synthesis.…”
Section: Discussionmentioning
confidence: 99%
“…Both of these enzymes catalyze the synthesis of substrates utilized by DGAT2 for TG synthesis. FATP1 possesses acyl CoA synthetase activity and activates fatty acids for DGAT2 (24,39). SCD1 converts saturated fatty acyl CoAs to monounsaturated acyl CoAs which are abundant in TG (40).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are surrounded by a PL monolayer mainly containing PC and PE (Bartz et al 2007). Because the ratio between TAG and PC could be an important determinant of LD size (Krahmer et al 2011;McFie et al 2011;Xu et al 2012), LDs were visualized in the sams-1 mutants through 3D fluorescence imaging. Adult sams-1 mutants formed enlarged intestinal LDs that dramatically differed from those observed in wild-type worms (Fig.…”
Section: Sams-1 Mutants Exhibit Enlarged Lipid Droplets Throughout Thmentioning
confidence: 99%